Risk factors for nonalcoholic steatohepatitis in cryptogenic cirrhosis - Leite,Andrea Benevides (2012)
CONTEXT: In about 10% of patients with chronic liver disease, it is not possible to identify an etiologic factor. These cases are called cryptogenic cirrhosis. Currently, nonalcoholic steatohepatitis (NASH) is being considered as a possible etiologic factor for a significant segment of patients that presents with cryptogenic cirrhosis. OBJECTIVE: To estimate the prevalence of risk factors for NASH in patients with cryptogenic cirrhosis, in order to verify if there is a causal relationship between them. METHOD: Cross-sectional study, with evaluation of the demographic and laboratorial data of patients with cryptogenic cirrhosis. They were compared with data obtained from a group with NASH and a group with alcoholic and/or hepatitis C (HCV) cirrhosis. RESULTS: Forty seven patients with cryptogenic cirrhosis were evaluated, 47 with NASH and 196 with HCV and/or alcoholic cirrhosis. The mean age of patients with cryptogenic cirrhosis was 52 years, while in those with NASH it was 46.4 years (P = 0,041). The group with cryptogenic cirrhosis had 23 female and 24 male patients. Of the patients who presented with NASH, 68.1% were female. Of the patients who presented with alcoholic/HCV cirrhosis, 64.8% were male. There were no statistically significant differences between the groups. In cryptogenic cirrhosis patients, the following prevalences could be observed: impaired fasting glycemia - 68.2%; obesity - 27.5%; total hypercholesterolemia - 27.9%; low HDL levels - 58.1% (women - 81%; men - 36.4%); hypertriglyceridemia - 16.3%. The results seen in cryptogenic cirrhosis patients showed statistical similarity with the results of the NASH group regarding fasting glycemia (62.8%) and male HDL levels (53.8%). The comparison with the alcoholic/HCV cirrhosis group showed statistical differences regarding fasting glycemia (45.2%), hypercholesterolemia (13.3%) and female HDL levels (50.8%). CONCLUSIONS: It is not possible to establish a causal relationship between cryptogenic cirrhosis and NASH. Only data related to fasting glycemia and HDL levels in male patients showed statistical similarities between both groups of patients.